2018
DOI: 10.1128/aem.01865-18
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Plant Growth Promotion by Volatiles of Root-Associated Microbacterium spp

Abstract: Volatile compounds produced by plant-associated microorganisms represent a diverse resource to promote plant growth and health. Here, we investigated the effect of volatiles from root-associated species on plant growth and development. Volatiles of eight strains induced significant increases in shoot and root biomass of but differed in their effects on root architecture. strain EC8 also enhanced root and shoot biomass of lettuce and tomato. Biomass increases were also observed for plants exposed only briefly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 67 publications
3
62
0
2
Order By: Relevance
“…The study revealed that even a brief exposure of bacterial VOCs also stimulated plant growth suggesting that these can be used to prime crops without direct and prolonged exposure of plants to bacteria. Moreover, it was also demonstrated that the VOC mediated plant growth promotion was tissue specific and showed biomass increment only in plants exposed to volatiles via roots (Cordovez et al, 2018). Two bacterial volatiles, 4-nitroguaiacol, and quinoline produced by salt-tolerant Pseudomonas simiae were reported to induce soybean growth under 150 mM salt stress (Vaishnav et al, 2016).…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…The study revealed that even a brief exposure of bacterial VOCs also stimulated plant growth suggesting that these can be used to prime crops without direct and prolonged exposure of plants to bacteria. Moreover, it was also demonstrated that the VOC mediated plant growth promotion was tissue specific and showed biomass increment only in plants exposed to volatiles via roots (Cordovez et al, 2018). Two bacterial volatiles, 4-nitroguaiacol, and quinoline produced by salt-tolerant Pseudomonas simiae were reported to induce soybean growth under 150 mM salt stress (Vaishnav et al, 2016).…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…Remarkably, without direct physical contact with plants, micro‐organisms, such as fungi and bacteria, can also affect plant growth and defence through the emission of volatile organic and inorganic compounds (Kanchiswamy, Malnoy, & Maffei, 2015; Piechulla, Lemfack, & Kai, 2017; Tyagi, Mulla, Lee, Chae, & Shukla, 2018). Volatiles emitted by pathogenic and beneficial micro‐organisms can promote plant growth (Casarrubia et al., 2016; Cordovez et al., 2018; Fincheira & Quiroz, 2018; Moisan et al., 2019), and accelerate plant development (Moisan et al., 2019; Sánchez‐López et al., 2016), for instance by increasing nutrient uptake (Liu & Zhang, 2015) or by altering phytohormone homoeostasis (Bailly & Weisskopf, 2012; Zhang et al., 2007). Microbial volatiles can also enhance plant resistance to fungal, bacterial or oomycete pathogens (Farag, Zhang, & Ryu, 2013; Jain, Varma, Tuteja, & Choudhary, 2017; Kottb, Gigolashvili, Großkinsky, & Piechulla, 2015) and to insect herbivores (Aziz et al., 2016; Cordovez et al., 2017; Moisan et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the precolonization phase, before direct contact with plants occurs, beneficial bacteria and fungi emit diffusible substances (e.g., carbohydrates, proteins, fatty acids, flavonols, organic acids, amino acids and hormones) that cause massive lateral root (LR) formation and enhanced root hair (RH) growth, thus improving the root's capacity to explore for water and minerals and predisposing plants to microbial colonisation and infection (Contreras‐Cornejo, Macías‐Rodríguez, Cortés‐Penagos, & López‐Bucio, 2009; López‐Bucio et al, 2007). These microorganisms also emit a large number of volatile compounds (VCs) with molecular masses of less than 300 Da that promote growth and photosynthesis, induce systemic drought tolerance, improve nutrient acquisition, and modulate RSA in both host and non‐host plants (Cho et al, 2008; Cordovez et al, 2018; Ditengou et al, 2015; Gutiérrez‐Luna et al, 2010; Ryu et al, 2003; Zhang et al, 2009, 2010). Recent studies have shown that this capacity is not restricted to beneficial microbes; it also extends to phytopathogens and microbes that do not normally interact mutualistically with plants (Cordovez et al, 2017; García‐Gómez et al, 2019; Li et al, 2018; Moisan et al, 2019; Sánchez‐López, Baslam, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…RSA modulation by microbial VCs has frequently been associated with lipophilic carbon‐based compounds, which are known as volatile organic compounds (VOCs) (Bitas et al, 2015; Cordovez et al, 2018; Ditengou et al, 2015; Garnica‐Vergara et al, 2016; Gutiérrez‐Luna et al, 2010; Splivallo, Fischer, Göbel, Feussner, & Karlovsky, 2009; Zhang et al, 2007, 2008). In addition to VOCs, microorganisms also release a limited number of volatile inorganic compounds (VICs) with molecular masses of less than 45 Da such as hydrogen sulfide (H 2 S), molecular hydrogen, nitric oxide (NO), nitrogen dioxide, nitrous oxide and carbon monoxide (CO) (García‐Gómez et al, 2019; Nandi & Sengupta, 1998; Shatalin, Shatalina, Mironov, & Nudler, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation